2016
DOI: 10.1080/03079457.2016.1168514
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathomorphological, bacteriological and serological examination of broiler breeders and pheasants experimentally infected withOrnithobacterium rhinotracheale

Abstract: The aim of the investigations was to determine the influence of Ornithobacterium rhinotracheale (ORT) on the development of pathomorphological lesions in the respiratory organs and on the health status of experimentally infected broiler breeders and pheasants from the rearing stage. There was no evidence of clinical signs in infected broiler breeder hens nor in the group of infected pheasants except for one bird in the latter group which exhibited slower movement and gasping. The frequency and intensity of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…Of note, chickens and pheasants belong to the same family. The results showed a high similarity in the kinetics of serological responses for both species after infection, also confirming the use of this test in pheasants [24].…”
Section: Serotyping and Detectionsupporting
confidence: 74%
See 2 more Smart Citations
“…Of note, chickens and pheasants belong to the same family. The results showed a high similarity in the kinetics of serological responses for both species after infection, also confirming the use of this test in pheasants [24].…”
Section: Serotyping and Detectionsupporting
confidence: 74%
“…Factors, such as management, environmental stressors, or the presence of other pathogens, can play an important role in the disease manifestation [12]. Gavrilović et al [24] have demonstrated that natural monoinfections with ORT are less aggressive than those from experimental challenge. Experimental studies of monoinfection with ORT showed that ORT had less effect on hens than on pheasants, suggesting it is host dependent, although both species belonged to the same Phasianinae subfamily.…”
Section: Mode Of Infection and Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies also agreed with us based on their results [38]. We also found that a cycle threshold value of diffraction existed between the samples due to the differentiation of ORT's DNA in the sample [39].…”
Section: Detection Of Ort In Using the Direct Methodssupporting
confidence: 89%
“…The pathological changes that are observed in ornithobacteriosis are usually localized to the lungs, and include thickening of the interstitial tissue, edema, effusion of exudate, fibrin, and heterophilic infiltration. In the trachea, as a rule, no specific pathological changes are observed, only sometimes lymphocytic, mononuclear infiltration of the mucous membrane, hyperplasia of the glandular epithelium are recorded (Gavrilović et al, 2015). A significant variation in the serovars of the pathogen and their variability significantly complicates the diagnosis of the disease in industrial poultry farming.…”
Section: Introductionmentioning
confidence: 99%